Caspase levels and execution efficiencies determine the apoptotic potential of the cell. - Florentin, A.; Arama, E. (Journal of Cell Biology, 2012)
Essentially, all metazoan cells can undergo apoptosis, but some cells are more sensitive than others to apoptotic stimuli. To date, it is unclear what determines the apoptotic potential of the cell. We set up an in vivo system for monitoring and comparing the activity levels of the two main effector caspases in Drosophila melanogaster, Drice and Dcp-1. Both caspases were activated by the apoptosome after irradiation. However, whereas each caspase alone could induce apoptosis, Drice was a more effective inducer of apoptosis than Dcp-1, which instead had a role in establishing the rate of cell death. These functional differences are attributed to their intrinsic properties rather than merely their tissue specificities. Significantly, the levels of the procaspases are directly proportional to their activity levels and play a key role in determining the cell's sensitivity to apoptosis. Finally, we provide evidence for the existence of a cellular execution threshold of caspase activity, which must be reached to induce apoptosis.